2018
DOI: 10.3126/nje.v7i4.20627
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy and years of life lost in HIV patients under the care of BandarAbbas Behavioral Disorders Counseling Center

Abstract: Background:HIV epidemic is mostly targeted adults and has numerous negative health, social, economic, cultural and political consequences. In this study Life Expectancy (LE) and Average Years of Life Lost (AYLL) in HIV/AIDS patients are estimated.Materials and Methods:In this descriptive study all the patients at the age of 18 and more under the care of BandarAbbas Behavioral Disorders Counseling Center (BBDCC) during 2005-2015 are included. The town of BandarAbbas is center of Hormozgan Province in southern I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…The questionnaire was rated on a 5-point Likert-type scale ranging from very high to no effect. The sections of personal barriers, medication challenges, quality of service delivery, financial problems, perceived support, and disease disclosure included, respectively, eight items (range of 8-40), six items (range of 6-30), six items (range of 6-30), two items (range of 2-10), four items (range of 4-20), and four items (range of [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Validity and reliability of the questionnaire were previously substantiated.…”
Section: Adherence To Art Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire was rated on a 5-point Likert-type scale ranging from very high to no effect. The sections of personal barriers, medication challenges, quality of service delivery, financial problems, perceived support, and disease disclosure included, respectively, eight items (range of 8-40), six items (range of 6-30), six items (range of 6-30), two items (range of 2-10), four items (range of 4-20), and four items (range of [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Validity and reliability of the questionnaire were previously substantiated.…”
Section: Adherence To Art Questionnairementioning
confidence: 99%
“…Despite the fact that most patients are aware of the importance of medical therapy in improving their quality of life and increasing their life expectancy, the MA in these patients is not at an optimal level, and as mentioned in Iran, the level of MA is far from optimal 4,19 . Bandar Abbas, the largest commercial port in Iran, located in Hormoz Strait adjacent to the Persian Gulf countries, accepts many immigrants from different parts of Iran and other countries for various commercial and industrial jobs 20 . In this region, there is a high rate of risky behaviors 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LYL has been infrequently estimated for HIV/AIDS, as noted in one study [11], which measured LYL among a population in Iran and found HIV/AIDS patients had 46 fewer years of life expectancy at age 20 than the general population. Another study [12] used the USA population-based National HIV Surveillance System data to estimate life expectancy and average years of life lost (LYL) among persons aged 13 years or older from all 50 states and Washington, D.C., diagnosed with HIV infection during 2008-2011.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, the insufficient number of economic studies on HIV is evident to find community-based and costeffective programs (23). Given the lack of financial resources in health systems in developing countries, costeffectiveness analysis of both active and passive screening methods can help clarify the economic outcomes of these methods and also helps the policymakers and program managers to make informed decisions about resource allocation, thus allowing them to choose the most effective and efficient method by considering available resources through reviewing alternatives to achieve their goals.…”
Section: Introductionmentioning
confidence: 99%